Self-medication with antibiotics among patients attending a Malaysian primary care clinic: a preliminary study - Zubaidi, Zati Sabrina Ahmad (International Journal Of Community Medicine And Public Health, 2021)
Background: Research on self-medication with antibiotic in Malaysian primary care clinics are limited. This study aimed to assess the practice of self-medication with antibiotic, self-recognized complaints to self-medicate, antibiotic knowledge, attitudes towards antibiotic and potential association to self-medicate in a primary care clinic. Methods: This was a community-based pilot study using a self-administered questionnaire among 281 respondents. Chi square test and independent T test were performed to identify potential associations to self-medication. Results: The prevalence of self-medication with antibiotic was 13.3%. The most common complain to self-medicate was for upper respiratory tract infection (58.8%). Majority of them were able to self-purchased antibiotics (55.9%). 70.6% of respondents who SMA understood that overuse of antibiotic results in antibiotic resistance. Interestingly, antibiotic knowledge among respondents who self-medicate was higher (6.50±1.93) compared to those who did not (5.85±2.46) albeit not statistically significant. However, respondents who self-medicate had poorer attitude towards antibiotic compared to those who did not and this was statistically significant, t (254)=0-4.25, p=0.0001. 95% CI (-4.653, 1.709). This includes keeping antibiotics at home and using leftover antibiotics for respiratory illness. Conclusions: Self-medication with antibiotic in this population is low. Inappropriate attitude towards antibiotic is associated with self-medication with antibiotic. Antibiotic campaigns should focus on improving the community’s attitude towards antibiotic especially pertaining to educating the public against keeping antibiotic at home and using leftover antibiotics for upper respiratory tract infection. The findings demonstrated the need and feasibility of the study protocol for future research.